The Effect of Budget Preparation Participation on Employee Performance at the Mataram City Regional Financial Agency - Ardini, Komala Septi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Participation in budget preparation at the Mataram City Regional Financial Agency is the focus of this research, which aims to assess its influence on employee performance. This research uses descriptive statistics, reliability and validity tests, multicollinearity and heteroscedasticity tests, simple regression tests, and coefficient of determination, as well as reliability and validity tests, all of which were carried out via SPSS. A total of 53 participants filled out the survey which is a data collection technique. The performance of employees at the Mataram City Finance Agency is positively and significantly influenced by their involvement in budget preparation, according to research results.